Emerging Roles for Chromo Domain Proteins in Genome Organization and Cell Fate in C. elegans - DasGupta, Abhimanyu (Front Cell Dev Biol, 2020)
In most eukaryotes, the genome is packaged with histones and other proteins to form chromatin. One of the major mechanisms for chromatin regulation is through post-translational modification of histone proteins. Recognition of these modifications by effector proteins, often dubbed histone “readers,” provides a link between the chromatin landscape and gene regulation. The diversity of histone reader proteins for each modification provides an added layer of regulatory complexity. In this review, we will focus on the roles of chromatin organization modifier (chromo) domain containing proteins in the model nematode, Caenorhabditis elegans. An amenability to genetic and cell biological approaches, well-studied development and a short life cycle make C. elegans a powerful system to investigate the diversity of chromo domain protein functions in metazoans. We will highlight recent insights into the roles of chromo domain proteins in the regulation of heterochromatin and the spatial conformation of the genome as well as their functions in cell fate, fertility, small RNA pathways and transgenerational epigenetic inheritance. The spectrum of different chromatin readers may represent a layer of regulation that integrates chromatin landscape, genome organization and gene expression.